الأسواق المالية الناشئة ودورها في تنمية الاقتصاد الوطني "سورية, دراسة تحليلية استشرافية" - بو حسون ياسر; زهرة شادي أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يتناول هذا البحث بالدراسة والتحليل مسألة الأسواق المالية (البورصات) ودورها في تنمية الاقتصاد الوطني وبصورة خاصة في البلدان النامية. ويتطرق البحث إلى بيان الأساس النظري للأسواق المالية وأقسامها المختلفة وإجراءات التعامل فيها, ثم التعريف بالأوراق المالية المتداولة فيها وأنواعها وطبيعتها, ومن ثم مساهمة الأسواق المالية في التنمية الاقتصادية، ودراسة الأزمات التي تعرضت لها بعض الأسواق المالية الناشئة مع دراسة نظرية لواحدة من هذه الأسواق وذلك من اجل الاستفادة من هذه التجارب في إقامة سوق للأوراق المالية في بلدنا. ثم يتناول البحث تحليل الاقتصاد السوري بهدف الوقوف على بعض النقاط السلبية التي تشكل عقبة في وجه إقامة سوق للأوراق المالية في سوريه, مع التطرق إلى الخطوات المتخذة من قبل الحكومة لإقامة سوق للأوراق المالية في سوريه. ويخلص البحث إلى بعض النتائج والمقترحات التي تهدف إلى تقديم بعض الحلول بهدف الوصل إلى إقامة سوق للأوراق المالية تتمتع بقدر كبير من الكفاءة بما يسهم في جعل هذه السوق محركاً لعجلة النمو الاقتصادي وليس مثبطاً لها. This research studies and analyzes the issue of financial market (stock exchange) and its role in developing national economy especially in undeveloped countries. The research shows the theoretic basis of the financial markets; its different parts and procedures dealing with it; the identification of current securities as well as its parts and nature; the paper then deals with investing in those financial markets focusing on the financial contribution in the economic development and with studying the crisis which some financial markets faced, including a theoretical study of one of those markets to make use of those experiences in making a financial market in our country. The research analyzes then the Syrian economy that aims to consider the negative points which might be obstacles in making such financial markets in our country as well as the achieved procedures by the government to make that kind of markets in Syria. The research concludes with some results and suggestions that aim to give some solutions to make a well-qualified financial market which contributes to increase the economic development but not to decrease it.